2020
DOI: 10.1186/s43141-020-00077-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant or pro-oxidant and glutathione transferase P1-1 inhibiting activities for Tamarindus indica seeds and their cytotoxic effect on MCF-7 cancer cell line

Abstract: Background The multidrug resistance (MDR) of cancer cells is a major obstacle to cancer treatment. Glutathione S-transferase Pi (GSTP1-1) catalyzes the conjugation of glutathione with anticancer drugs and therefore reduces their efficacy. Phenolic compounds have the potential to inhibit GST P1-1 activity, which is a promising goal to overcome MDR and increase the efficacy of chemotherapy. Results Three fractions (dichloromethane, ethyl acetate, and n-butanol) were prepared from Tamarindus indica seeds to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Guneidy et al examined protein levels of GST by using a CDNB substrate on breast cancer cell lines. Their comparison of increased GST A1 activities were found to have much similarity with our study [18]. Aybek et al investigated the effects of chemotherapeutic agents tamoxifen and 5-FU on MCF-7 cell line and human erythrocyte GST, an important enzyme of intracel-lular antioxidant metabolism.…”
Section: Discussionsupporting
confidence: 85%
“…Guneidy et al examined protein levels of GST by using a CDNB substrate on breast cancer cell lines. Their comparison of increased GST A1 activities were found to have much similarity with our study [18]. Aybek et al investigated the effects of chemotherapeutic agents tamoxifen and 5-FU on MCF-7 cell line and human erythrocyte GST, an important enzyme of intracel-lular antioxidant metabolism.…”
Section: Discussionsupporting
confidence: 85%
“…Guneidy et al ( 30 ) showed that there were large preventive effects and small cytotoxic effects of flavonoids on various cancer cell lines, for instance, the MCF-7 cell line. Flavonoids were also effective against A549, and HCT-116.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a complex disease which is a result of interplay of genetics, epigenetics, environment and lifestyle choices. Common cancer treatment options include chemotherapy, radiotherapy, surgery, and in some cases a joint therapy has shown encouraging results [ 1 ]. Non-Hodgkin’s lymphoma (NHL), a B cell lymphoma, is the most common type of lymphoma contributing to 80% of all lymphomas.…”
Section: Introductionmentioning
confidence: 99%